Introduction of a Research component in the undergraduate medical curriculum – Review of a trend - Sreedharan, Jayadevan (Nepal Journal of Epidemiology, 2012)
The question of whether a research component should be an integral part of medical curriculum has been debated in the past and is still controversial. Patient care is the most important aspect of a medical graduate but teaching, administration and research are also essential aspects. The implementation of a research component is more important at a student level as it helps to develop a judicious insight in their academic and clinical practice, which every medical person should possess. DOI: http://dx.doi.org/10.3126/nje.v2i3.6901 Nepal Journal of Epidemiology 2012;2(3):200-4